La imagen de América Latina en las letras húngaras y la presencia de la literatura húngara en América Latina : un esbozo - Tóth, Éva (Acta Hispanica, 2011)
The author, who is a poet, editor, and literary translator is one of those who have done a lot to make Latin American literature known in Hungary, and Hungarian literature known in Latin America. The study gives a brief overview of some of the most important characteristics of this so far little researched topic as well as provides some examples of the main representatives.